Image‐guided cranial irradiation‐induced ablation of dentate gyrus neurogenesis impairs extinction of recent morphine reward memories. Issue 8 (18th February 2019) - Rivera, Phillip D.; Simmons, Steven J.; Reynolds, Ryan P.; Just, Alanna L.; Birnbaum, Shari G.; Eisch, Amelia J.
Abstract: Dentate gyrus adult neurogenesis is implicated in the formation of hippocampal‐dependent contextual associations. However, the role of adult neurogenesis during reward‐based context‐dependent paradigms—such as conditioned place preference (CPP)—is understudied. Therefore, we used image‐guided, hippocampal‐targeted X‐ray irradiation (IG‐IR) and morphine CPP to explore whether dentate gyrus adult neurogenesis plays a role in reward memories created in adult C57BL/6J male mice. In addition, as adult neurogenesis appears to participate to a greater extent in retrieval and extinction of recent (<48 hr posttraining) versus remote (>1 week posttraining) memories, we specifically examined the role of adult neurogenesis in reward‐associated contextual memories probed at recent and remote timepoints. Six weeks post‐IG‐IR or Sham treatment, mice underwent morphine CPP. Using separate groups, retrieval of recent and remote reward memories was found to be similar between IG‐IR and Sham treatments. Interestingly, IG‐IR mice showed impaired extinction—or increased persistence—of the morphine‐associated reward memory when it was probed 24‐hr (recent) but not 3‐weeks (remote) postconditioning relative to Sham mice. Taken together, these data show that hippocampal‐directed irradiation and the associated decrease in dentate gyrus adult neurogenesis affect the persistence of recently—but not remotely—probed reward memory. These data indicate a novel role for adult neurogenesis in reward‐based memories and particularly the extinction rate of these memories. Consideration of this work may lead to better understanding of extinction‐based behavioral interventions for psychiatric conditions characterized by dysregulated reward processing.